(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine the legal protection of holders of replacement certificates of title to land, and to find out the obstacles faced in the Issuance of Land Replacement Certificates by the National Land Agency Office of Makassar City. This research uses an empirical legal research method that focuses more on The reality of law and society The results of this study indicate that legal protection for holders of certificates of replacement of title to land has followed the implementation of the provisions of Government Regulation Number 24 of 1997 concerning land registration which is closely related to UUPA because it adheres to a negative publication system that contains positive elements. And the obstacles found in the procedure for issuing a replacement certificate came from the Land Agency that lacks human resources who are experts in the field of certification and also from the applicant who does not know the procedure for issuing a replacement certificate of title to land. Abstrak: Penelitian ini bertujuan untuk mengetahui perlindungan hukum terhadap pemegang sertifikat pengganti hak milik atas tanah , dan untuk mengetahui kendala yang dihadapi dalam Pelaksanaan Penerbitan Sertifikat Pengganti Hak Milik atas Tanah oleh Kantor Badan Pertanahan Nasional Kota Makassar Penelitian ini menggunakan metode penelian Hukum secara Empiris yang lebih memfokus pada realita hukum dan masyarakatHasil penelitian ini menunjukkan bahwa perlindungan hukum terhadap pemegang sertifikat pengganti hak milik atas tanah sudah mengikuti pelaksanakan ketentuan dari Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran tanah yang sangat erat kaitannya dengan UUPA karena menganut sistem publikasi negatif yang mengandung unsur positif. Dan kendala yang ditemukan dalam prosedur penerbitan sertifikat pengganti berasal dari pihak Kantor Badan Pertanahan yang kurang sumber daya manusia yang ahli dibidang persertifikatan dan juga dari pihak pemohon hak yang kurang mengetahui prosedur penerbitan sertifikat pengganti hak milik atas tanah